Characterization of Pantoea ananatis Isolated from Garlic and Shallot - Nanik Nurjanah; Tri Joko; Siti Subandiyah (Universitas Gadjah Mada, 2017)
The new disease on garlic (Allium sativum) and shallot (A. cepa L. aggregatum group) have been found in several production centers of garlic and shallot in Tawangmangu and Temanggung, Central Java. The infected plants showed symptoms of leaf blight accompanied by chlorosis. The objective of this study was to determine the pathogen that causes leaf blight and chlorosis based on the phenotypic characterization and gyrB gene sequences analysis. The research started from the isolation of pathogen, physiological and biochemical test, DNA extraction, and sequence analysis of gyrB using gyrB 01-F and gyrB 02-R primer. The results showed that the isolated bacterial pathogen have a yellow pigment, slimy colonies with regular borders, convex, gram-negative, non-spore, facultative anaerobic, motile, catalase production, indole production, and acid production from D-glucose, D-mannitol, sucrose, and lactose. From the pathogenicity test, it was found that the bacteria produced the typical symptom of leaf blight. Characterization of pathogens based on gyrB gene sequence revealed that the pathogen was placed in the group of Pantoea ananatis. IntisariPenyakit baru pada bawang putih (Allium sativum) dan bawang merah (A. cepa L. aggregatum group) telah ditemukan di beberapa sentra produksi bawang putih dan bawang merah di Tawangmangu dan Temanggung, Jawa Tengah. Tanaman yang terinfeksi menunjukkan gejala hawar daun disertai klorosis. Tujuan penelitian untuk mengetahui karakter patogen berdasarkan fenotipik dan sekuen gen gyrB. Penelitian dimulai dengan isolasi bagian tanaman yang sakit, uji fisiologi dan biokimia, ekstraksi DNA dengan metode CTAB/NaCl dan amplifikasi gen gyrB menggunakan primer gyrB 01-F and gyrB 02-R. Hasil uji menunjukkan koloni berlendir, cembung, pigmen berwarna kuning, gram negative, tidak berspora, aerob fakultatif, motil, produksi katalase, indol, membentuk asam dari D-glukosa, D-monnitol, sukrosa dan laktosa, dan patogenesitas positif. Karakterisasi patogen berdasarkan sekuen gen gyrB, menunjukkan patogen hawar daun berkerabat dekat dengan Pantoea ananatis.